FRI0040 A Novel Approach to Quantify Morning Stiffness in Patients with Rheumatoid Arthritis. (9th June 2015) - Boeth, H.; Duda, G.; Hinzmann, D.; Hermann, S.; Taylor, W.; Ehrig, R.; Witaschek, T.; Buttgereit, F.
Abstract : Background: In addition to joint swelling and tenderness, patients with rheumatoid arthritis (RA) commonly experience morning symptoms of joint stiffness associated with pain that result in impaired function causing morbidity and productivity loss with early disease as well as those with low disease activity or remission 1 . However, the degree of morning stiffness has never been described. Objectives: Although RA patients recognize morning stiffness as being one of the four most significant symptoms to manage, validated morning stiffness patient-reported outcome (PRO) measures are lacking. Therefore, we have developed an approach to objectively quantify finger joint stiffness. The device has been approved by the ethical committee for the use in patients, and has also already obtained a national technical certification. We here present the first results of an ongoing study with this device. Methods: So far, nine female postmenopausal RA patients affected by morning stiffness of at least one hour agreed to participate in this study and underwent repetitive measurements of evening and on following morning cycle. These measurements quantified the passive resistance of an affected MCP joint against an externally applied torque while the finger was fixed in the device and passively moved from a completely extended position (referred to as 0°) to a flexed position of 60°. Measurement related sensors and advanced analysis algorithms for the investigation of resulting hysteresis curves enabled both the stiffness and dissipated energy to be evaluated at definite flexion-extension angles. A one-way ANOVA was then applied to test for differences in both parameters between repetitive evening and morning measurements. Results: The stiffness of the MCP joint (given in Nm/°) showed highest absolute values at extreme positions, i.e. at 0° and 60°, while lower values were detected at angles in between (Figure 1 ). At all flexion angles except 0°, stiffness was – as expected – always more pronounced in the morning (red bars) compared with evening measurements (blue bars). The difference found at 40° was statistically significant (p=0.038). Similar results (not shown) were obtained for dissipated energy with a significantly higher value in the morning than in the evening at a flexion angle of 50° (p=0.047). Conclusions: Even though the number of patients examined was low and the individual variation of absolute values between subjects is (known to be) considerable, our findings indicate that our approach is capable to differentiate stiffness and dissipated energy in the morning from that measured in the evening. The quantification of these parameters offers for the first time an option for objective evaluation the possibility to objectively evaluate and quantify this important patient-reported outcome in RA. Furthermore, such biomechanical assessments are also very likely able to quantify treatment effects on morning stiffness in the future. References: Da Silva, JAP et al.: Impact of impaired morning function on the lives and well-being of patients with rheumatoid arthritis. Scand J Rheumatol. Vol. 125 (2011), pp. 6-11. Acknowledgements: This study was funded by Horizon Pharma, USA. Disclosure of Interest: H. Boeth: None declared, G. Duda: None declared, D. Hinzmann: None declared, S. Hermann: None declared, W. Taylor: None declared, R. Ehrig: None declared, T. Witaschek: None declared, F. Buttgereit Grant/research support from: Dr. Buttgereit received consultancy fees, honoraria and travel expenses from Merck Serono, Horizon Pharma (formerly Nitec Pharma) and Mundipharma International Ltd, and grant support from Merck Serono and Horizon Pharma